2023
DOI: 10.14736/kyb-2023-3-0342
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-time safe tracking control of uncertain high-order nonlinear pure-feedback systems via unified transformation functions

Abstract: In this paper, a fixed-time safe control problem is investigated for an uncertain high-order nonlinear pure-feedback system with state constraints. A new nonlinear transformation function is firstly proposed to handle both the constrained and unconstrained cases in a unified way. Further, a radial basis function neural network is constructed to approximate the unknown dynamics in the system and a fixed-time dynamic surface control (FDSC) technique is developed to facilitate the fixed-time control design for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…If the nonlinear second-order neutral differential equation satisfies the Conditions (1)-( 3), there is a solution to the initial problem [24][25][26][27]. From Condition (1), it can be found that ∃ε > 0 makes f bounded on [0, ε ] × B(x 0 , ε) × B(x 0 , ε), so there is a constant M 0 , which makes:…”
Section: Solution Of Nonlinear Second Order Neutral Differential Equa...mentioning
confidence: 99%
“…If the nonlinear second-order neutral differential equation satisfies the Conditions (1)-( 3), there is a solution to the initial problem [24][25][26][27]. From Condition (1), it can be found that ∃ε > 0 makes f bounded on [0, ε ] × B(x 0 , ε) × B(x 0 , ε), so there is a constant M 0 , which makes:…”
Section: Solution Of Nonlinear Second Order Neutral Differential Equa...mentioning
confidence: 99%
“…However, developing numerical and exact solutions to these equations is crucial in applied mathematics and theoretical physics [19][20][21]. Consequently, innovative methods have been developed for analytical solutions that closely approximate the exact solutions [22,23]. Differential equations were often solved using integral transforms.…”
Section: Introductionmentioning
confidence: 99%
“…The research articles cited encompass a diverse range of topics within the field of control systems, vibration isolation, and neural network approximation. Guo et al delve into fixed-time safe tracking control and nonsingular fixed-time tracking control of uncertain nonlinear systems [16,17] 3. Lu et al focus on nonlinear vibration isolation systems with high-static-low-dynamic stiffness [18,19].…”
Section: Introductionmentioning
confidence: 99%